Modeling of Fast Neutral Atoms Flow Generation in Channel Rays of Glow Discharge - D. Volpian, O.; I. Kuzmichev, A.; A. Obod, Yu.; S. Sigov, A. (International Journal of Engineering and Technology, 2018)
A physical-kinetic approach has been used for modeling of fast neutral atoms flow generation in the channel rays of abnormal glow discharge. The fast atoms are generated due to charge exchange of ions accelerated by voltage drop on the cathode layer of positive space charge. The limits of applicability of the created model and the range of operating parameters of the fast atom source are established for the Ar (gas) – Ta (cathode) pair. The work is directed towards implementation of the beam processing of dielectric optical nanostructured metamaterials with help of fast neutral atoms.